Communication Strategies of Small Enterprises in Ukraine: Challenges and Features in Wartime - Yushchyshyna, Larysa Oleksiivna; Hulchak, Oleksandr Mykolaiovych (MDPC Publishing, 2024)
The article examines the features and challenges of communication strategies for small businesses in Ukraine during wartime. It explores how businesses adapt to new realities, including relocation, interaction with local markets, increased social responsibility, digitalization of communications, and flexible approaches. Based on the analysis of scientific sources, surveys, and interviews, effective strategies are identified to maintain business resilience, preserve customer trust, and develop new market opportunities. The findings can be useful for small businesses facing similar crisis conditions.
Keywords: small business; communication strategies; social responsibility